1995
DOI: 10.1530/jrf.0.1030279
|View full text |Cite
|
Sign up to set email alerts
|

The photoperiodic control circuit in euthyroid American tree sparrows (Spizella arborea) is already programmed for photorefractoriness by week 4 under long days

Abstract: The aim of this investigation was to determine whether spontaneous testicular regression in male American tree sparrows (Spizella arborea) that were thyroidectomized at week 4 of photostimulation manifests photorefractoriness, as it does in chronically photostimulated euthyroid controls. On the basis of our demonstration that exogenous thyroxine stimulates the gonads only when recipient birds are photosensitive, male tree sparrows were thyroidectomized at week 4 of photostimulation (20 h light:4 h dark) and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Alternatively, the protracted long-day requirement may indicate that our model merely requires refinement. Thus, long days may have two effects on the vernal component of seasonality: an early, interactive programming effect (with THs or a TH-dependent metabolite or ligand) [12,[14][15][16][17][18]26] and a later, independent permissive effect (current study), which creates a milieu appropriate for full expression of programmed testicular growth. Our assigning a postprogramming permissive role to long days corroborates the conclusion of Harris and Turek [27], namely, that after the testes of thyroid-intact white-throated sparrows have grown to a functional size (cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, the protracted long-day requirement may indicate that our model merely requires refinement. Thus, long days may have two effects on the vernal component of seasonality: an early, interactive programming effect (with THs or a TH-dependent metabolite or ligand) [12,[14][15][16][17][18]26] and a later, independent permissive effect (current study), which creates a milieu appropriate for full expression of programmed testicular growth. Our assigning a postprogramming permissive role to long days corroborates the conclusion of Harris and Turek [27], namely, that after the testes of thyroid-intact white-throated sparrows have grown to a functional size (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies on obligately photoperiodic American tree sparrows (Spizella arborea) lead us to conclude that THs and long days interact to program males for the vernal component of seasonality, as well as the autumnal component [12,[14][15][16][17][18]. By performing thyroidectomy (THX) before, at, or after the onset of photostimulation, we have demonstrated that programming for testicular growth occurs during the first week of photostimulation [16,18] and is independent of programming for photorefractoriness and postnuptial molt, which occurs between Weeks 1 and 3 [15,16,18]. These results provide strong support for the concept that vernal and autumnal events are independently controlled [1].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…We still do not know where THs or TH-dependent ligands exert their effect in the photoneuroendocrine system in the birds. Wilson and Reinert (35) suggest that THs interact somewhere between the photoreceptors and neuroendocrine cells in the brain. On the basis of what we do know in mammals, Bentley (33) points out that T 4 mediates nerve growth factor synthesis, which controls microtubule and axonal growth in the central nervous system, and this may in some way affect gonadotropinreleasing hormone secretion (32), which in turn influences LH/FSH secretion (33).…”
Section: Birdsmentioning
confidence: 99%